Shariah risk profiling through shariah based business modeling: A rectification plan for shariah audit finding (SNCR-01) for company xyz / Mohd Helmi Ahmad and Najahuddin Lateh - Lateh, Najahuddin (2017)
This paper is aims to discuss the Shariah risk based thinking aspects of Shariah compliant business entity within Malaysian Standard, Shariah Based Quality Management QMS1900:2015 (later on known as the ‘Standard’. It initially shares and examines one of Shariah Audit findings classified as Shariah non-conformity (SNCR-01) which is ‘Absence of Shariah based business models’ in the company dealing with its stakeholders internally and externally. Secondly, it will examine the status of SNCR-01 as one of Shariah risk profile method. The researchers found that the standard does not elaborate explicitly on the risk profiling in certain. It depends on the individual qualified Shariah advisor or officer to do so. Without it, the issue will remain unsolved. Due to the given facts and the mentioned method, the researchers propose that the any organisation (to be precise, the company) shall establish a Shariah based business models as an effort for risk profiling as a tool to mitigate the risk and subsequently establish a proper and sound corrective actions in its rectification plan in the event SNCR occurs in the future.